"Daughters of Gujarat in the diaspora": immigrant women, identity and agency in Natal - Hiralal, Kalpana (Faculty of Humanities, University of the Free State, 2013)
Through the narrative genre the author examines issues of identity and agency amongst 15 Gujarati Hindu immigrant women who arrived in Natal (South Africa) between 1943 and 1953. The aims of this article are three-fold: Firstly, through the narratives the author seeks to highlight the many socioeconomic challenges that immigrant Indian women faced in the diaspora. Secondly, issues of identity are examined in the context of “home” and “belonging”. While the author argues that Gujarat, their place of birth, is no longer perceived as their “homeland”, it plays an important role in constructing immigrant women’s ethnic identity. Thirdly, the article explores notions of agency and argues that given their personal, economic and social circumstances, Gujarati Hindu women were able to negotiate new roles for themselves within the household. Migration generated new challenges within the traditional household which resulted in some women exercising more agency than others. By examining notions of agency, this article seeks to dispel the myth of “passive”, “docile” Indian women, devoid of autonomy in their lives. It hopes to add to the current theoretical debates on immigrant women, agency and identity with reference to Gujarati speaking Hindu women in South Africa, a relatively unexplored area of research.
Keywords: Gujarati women; Immigrants; Identity; Agency; Indian; Diaspora; Ethnicity; Narratives